2022
DOI: 10.1590/1678-4324-2022220185
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vaccination on Covid-19 Dynamics in Brazil: A Fuzzy Approach

Abstract: The COVID-19 pandemic has spread widely through the world, since 2019. Then, the search for vaccines has become fundamental against the disease and has generated great expectations on population. In Brazil, the first case of COVID-19 was registered in February 2020 and the process of vaccination started in early 2021. In this context, considering the advance of vaccination and the behavior of epidemics, we present a study on the effect of population-wide vaccination on the evolution of the COVID-19 epidemic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, elderly-only vaccination, even without general interventions directed to reduce population transmission, is sufficient for dramatically reducing mortality. Stiegelmeier et al ( 24 ) proposed a p-fuzzy system in order to model the COVID-19 epidemic evolution under the effect of vaccination in Brazil. They concluded that the level of infestation tends to decrease as the number of people vaccinated increases.…”
Section: Introductionmentioning
confidence: 99%
“…However, elderly-only vaccination, even without general interventions directed to reduce population transmission, is sufficient for dramatically reducing mortality. Stiegelmeier et al ( 24 ) proposed a p-fuzzy system in order to model the COVID-19 epidemic evolution under the effect of vaccination in Brazil. They concluded that the level of infestation tends to decrease as the number of people vaccinated increases.…”
Section: Introductionmentioning
confidence: 99%